Effects of forming parameters and sintering schedules to the mechanical properties and microstructures of final components - Rahman, M.M.; Nor, S.S.M.; Rahman, H.Y.; Sopyan, Iis (Elsevier Ltd., 2012)
This paper presents the effects of forming parameters and sintering schedules to the mechanical properties and microstructures of products formed through warm compaction route. A lab scale warm compaction rig is designed and fabricated which enabled the generation of green compacts at different forming parameters. The feedstock was prepared by mechanically mixing the main powder constituent, i.e., iron ASC 100.29 powder with zinc stearate to reduce the die–wall as well as inter-particle frictions hence inhomogeneous density distribution could be avoided. The powder mass is formed at different temperature, i.e., 120 C and 180 C applying 130 kN axial loading simultaneously from top and bottom punches. The defect free green compacts were sintered in inert gas fired sintering furnace for different sintering schedules. The final products were characterized through density measurement, hardness test, and three point bending test whereas the microstructures were analyzed by Scanning Electron Microscopy (SEM). The results revealed that the properties of sintered parts formed at 180 C are better than those formed at 120 C. The suitable forming parameters and sintering schedules were identified from this study.